FEATURES OF BRINGING SMALL AND MEDIUM-SIZED BUSINESSES TO ADMINISTRATIVE RESPONSIBILITY - VASILYEVA O.N.; KESHISHIAN T.S. (Legal Bulletin)
The relevance of the chosen research topic is expressed in the active development of small and medium-sized businesses and, in this regard, the increase in the number of administrative offenses. The purpose of the study is to identify the main criteria, compliance with which is necessary to replace an administrative fine with a warning, as well as to analyze the practical application of such a legal mechanism. This article discusses the specifics of the application of the norms of Article 4.1.1 of the Code of Administrative Offences of the Russian Federation, as well as the interaction of this norm with Article 3.4. of the Code of Administrative Offences of the Russian Federation. To achieve this goal, general scientific methods were used, as well as methods of legal hermeneutics, comparative legal and formal legal methods. The study identifies the main problematic aspects of law enforcement of replacing administrative punishment in the form of an administrative fine with a warning, such as the ambiguity of judicial practice, the ambiguity of interpretation of legislative norms, etc. The main conclusion of the study is the need to expand the practice of replacing an administrative fine with a warning as a mitigation of punishment.